A holistic End-of-Life (EoL) Index for the quantitative impact assessment of CFRP waste recycling techniques - Markatos Dionysios N.; Katsiropoulos Christos V.; Tserpes Konstantinos I.; Pantelakis Spiros G. (Manufacturing Review, 2021)
In the present study, a holistic End-of-Life (EoL) Index is introduced to serve as a decision support tool for choosing the optimal recycling process among a number of alternative recycling techniques of CFRP waste. For the choice of the optimal recycling process, quality of the recycled fibers as well as cost and environmental impact of the recycling methods under consideration, are accounted for. Quality is interpreted as the reusability potential of the recycled fibers; that is quantified through the equivalent volume fraction of recycled fibers that balances the mechanical properties of a composite composed of a certain volume fraction of virgin fibers. The proposed Index is offering an estimated balanced score, quantifying a trade-off between the reusability potential of the recycled fibers as well as the cost and the environmental impact of the recycling methods considered.